2004
DOI: 10.1074/jbc.m313721200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Hypersensitivity of Fanconi Anemia Type C-deficient Cells Is Dependent on a Redox-regulated Apoptotic Pathway

Abstract: Fanconi anemia is a genetic disorder characterized by bone marrow failure. Significant evidence supports enhanced apoptosis of hematopoietic stem/progenitor cells as a critical factor in the pathogenesis of bone marrow failure in Fanconi anemia. However, the molecular mechanism(s) responsible for the apoptotic phenotype are incompletely understood. Here, we tested whether alterations in the activation of a redox-dependent pathway may participate in the pro-apoptotic phenotype of primary Fancc ؊/؊ cells in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 73 publications
5
90
0
Order By: Relevance
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionsupporting
confidence: 53%
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionsupporting
confidence: 53%
“…Ask1 plays an important role in the cell response to oxidative stress, being essential for the activation of the stressactivated protein kinase JNK (Gotoh and Cooper, 1998;Tobiume et al, 2001;Machino et al, 2003;Saadatzadeh et al, 2004;Kadowaki et al, 2005). As expected, exposure of HEK293 cells to H 2 O 2 induced the rapid phosphorylation of JNK ( Figure 1E), which was increased severalfold by pretransfecting the cells with a HA-tagged version of Ask1 (Ask1-HA) ( Figure 1A, lanes 3 and 4).…”
Section: In Vivo Oxidation Of Ask1 By H 2 Omentioning
confidence: 84%
“…Moreover, the role of inappropriate disulfide bond formation in the pathogenesis of human disease is relatively unknown. The physiological importance of maintaining key redox-sensitive proteins in a reduced state was recently demonstrated in studies showing that the Fanconi anemia group C protein increases the survival of hematopoietic progenitor cells by preventing disulfide bond formation and the concomitant inactivation of glutathione S-transferase P1 during apoptosis (30) in addition to preventing H 2 O 2 -induced activation of the redox-sensitive kinase ASK1 (57). The findings presented here highlight the pivotal role of cysteine oxidation and disulfide bond formation in many aspects of cell function during oxidative stress and should provide a basis for further exploration of the disulfide proteome.…”
Section: Discussionmentioning
confidence: 99%